The Annual Effective Dose for Some Food Crops Samples Using Alpha Track Detector - Yousef, Hesham A. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Radon gas arrives the indoors from different sources and very important in human life because it is harmful on the human population. Radon concentrations were measured in some crops samples from the local market by Suez government, Egypt, using alpha track detector from the type of CR-39. The values of the annual effective dose varied from 1.94 - 1.21mSvy-1. The obtained results indicate that the values of annual effective dose lower than the recommended limit of ICRP. We conclude that there is no health hazard due to radon gas, when used in eating of the food crops samples in this study. This work will help to provide an important database about the radiation hazard from food crops, which used in our houses.